2006
DOI: 10.1073/pnas.0511149103
|View full text |Cite
|
Sign up to set email alerts
|

Self-fulfilling cavitands: Packing alkyl chains into small spaces

Abstract: The present research was undertaken to determine the conformations of alkyl groups that are forced into small spaces. Unbranched alkyl groups assume fully extended conformations in the free space of solutions, because any bends in the structure create steric clashes between hydrogens along the chain. We synthesized a series of alkyl esters of a carboxylic acid attached to the inner surface of a vase-shaped container structure. The shorter esters (ethyl and propyl) can be accommodated in extended conformations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…In addition, AtzB differentiates between straight-chained N-alkyls and N-alkyl ethers like N-propyl-3-methoxy side chains [2-hydroxy-4-(N-isopropylamino)-6-N-(3-methoxypropylamino)-1,3,5-triazine]. Purse and Rebek found that alkyl group conformational changes, such as anti to gauche transitions, occurred readily in response to space limitations (22). These transitions occur if the binding energy supplied by attractions to the container's inner surface compensates for any conformational energetics.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, AtzB differentiates between straight-chained N-alkyls and N-alkyl ethers like N-propyl-3-methoxy side chains [2-hydroxy-4-(N-isopropylamino)-6-N-(3-methoxypropylamino)-1,3,5-triazine]. Purse and Rebek found that alkyl group conformational changes, such as anti to gauche transitions, occurred readily in response to space limitations (22). These transitions occur if the binding energy supplied by attractions to the container's inner surface compensates for any conformational energetics.…”
Section: Resultsmentioning
confidence: 99%
“…HRMS were measured on a JEOL JMS-T100CS AccuTOF. NMR spectra were taken on a Varian Inova 400 (400 MHz, 1 H and 2D spectra) instrument or on a Bruker DMX 300 (75 MHz, 13 C spectra) machine and were calibrated to an internal standard of tetramethylsilane (d = 0.00 ppm). Porphyrin macrocycle H 2 1 was synthesized according to a literature procedure.…”
Section: Experimental Section Materials and Methodsmentioning
confidence: 99%
“…The crude mixture was subjected to a flash silica column to obtain the corresponding primary alcohol. 2-Butylhexan-1-ol: [19b] Methylene solution: 10 (0.40 g, 2.9 mmol) in THF (30 mL); borane solution: 0.90 mL, 1.8 mmol; neutralization solutions: ethanol (6 mL), aqueous 3.0 m NaOH (35 mL) and aqueous 35 % H 2 O 2 (35 mL); eluent: n-pentane/diethyl ether, 9:1 (v/v); yield = 0.32 g as a colourless liquid (2.0 mmol, 69 %); 1 H NMR (400 MHz, CDCl 3 ): d = 3.54 (t, 2 H, HOCH 2 , J = 5.6 Hz), 1.45 (m, 1 H, HOCH 2 CH), 1.38-1.22 (m, 12 H, HOCH 2 -CHCH 2 CH 2 CH 2 ), 1.18 (t, 1 H, OH, J = 5.6 Hz), 0.90 ppm (t, 6 H, CH 3 , J = 7.2 Hz); 13 C NMR (75 MHz, CDCl 3 ): d = 65. 14, 40.00, 30.14, 28.62, 22.61, 13.57 ppm.…”
Section: -Methylene-pentadecane (11)mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, they reported an unusual hetero-guest inclusion by a hydrogen-bonded molecular capsule, with preferential accommodation of a molecule each of benzene and p-xylene [38]. Their self-assembled capsule also provides a medium for stabilization of reactive intermediates [39], to shift the equilibrium between two stereoisomers [40], or to regulate the conformation of a guest species [41]. They expanded their self-assembled cavitand capsules by the addition of appropriate spacers, permitting variation of guest selectivity, while also demonstrating attachment of a rotating door unit to the cavitands [42,43].…”
Section: Small Molecule Assemblymentioning
confidence: 99%